An Intelligent Wireless Modular System for Effective Disaster Management - Ramaswamy, Bhakthavathsalam (Discoveries in Agriculture and Food Sciences, 2016)
The impact of increasing urbanization has set an alarming concern of the consequences of loss of human lives in the event of a natural disaster such as floods. It is essential that disasters are detected at inception so that the severity of damage could be reduced by a greater extent. The readings received from the sensor at regular intervals are compared with the threshold and any increase is immediately updated to the user on the app. A graphical analysis indicates to the user the possible fluctuations of the parameters used for an appropriate inference of the situation at that instant. This system would be useful in detecting increasing water level, UV radiation, atmospheric pressure, temperature and humidity and keeping track of the situation real time monitoring the probability of an occurrence of disaster. The application could be deployed near traffic subways or underpasses that have stagnant water due to a heavy rainfall to divert traffic thereby reducing traffic snarls at major parts of the city. A common man having access to internet can visit the website created or who possesses a Smartphone can download the application thereby benefiting from the system. Another main objective of the system developed is data collection. New datasets can be developed which help in better predicting similar disaster situations in the future by sensing common patterns overtime. Several kinds of datasets can be generated as per the application. These datasets will prove a tool against better disaster management for the times to come.